1995
DOI: 10.1139/v95-217
|View full text |Cite
|
Sign up to set email alerts
|

The role of polymer flexibility on the interaction with surfactant micelles: poly(vinyl alcohol) and sodium dodecyl sulphate aqueous micelle interactions studied by dynamic fluorescence quenching

Abstract: Abstract:The interactions between poly(viny1 alcohol) and the surfactant sodium dodecyl sulphate in aqueous solutions have been investigated by means of static and dynamic fluorescence measurements. By static fluorescence measurements the onset of interaction, the critical aggregation concentration, is determined to be 6.5 mM at 20°C and 7.0 mM at 40°C. By dynamic fluorescence measurements without added quencher the influence on the lifetime of the fluorescent probe, pyrene, by the presence of the polymer is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The stabilizing performances of PVA and Pluronic F-127 were compared to each other in different practical systems and differences were assigned to the lower hydrophilicity and flexibility of PVA chains. [43] Particularly, Takasu et al [44] reported the CMC value of 8.0 × 10 −4 g.mL −1 for aqueous PVA solutions at room temperature through surface-tension measurements. As one can see, availability of CMC data of surfactants in complex reaction mixtures at actual reaction temperatures is scarce.…”
Section: Particles Produced By Sonifiermentioning
confidence: 99%
“…The stabilizing performances of PVA and Pluronic F-127 were compared to each other in different practical systems and differences were assigned to the lower hydrophilicity and flexibility of PVA chains. [43] Particularly, Takasu et al [44] reported the CMC value of 8.0 × 10 −4 g.mL −1 for aqueous PVA solutions at room temperature through surface-tension measurements. As one can see, availability of CMC data of surfactants in complex reaction mixtures at actual reaction temperatures is scarce.…”
Section: Particles Produced By Sonifiermentioning
confidence: 99%
“…In this respect, most aggregation numbers that have been reported were obtained at surfactant or polymer concentrations where the results were probably a weighted average due to a mixture of regular micelles and polymer-surfactant complexes in solution (29,30). Recently we have shown, for PEO-sulfate surfactant systems, that at high PEO concentration, [PEO] = 0.10 M, it is possible to obtain constant n values in the range of cac-psp (16).…”
Section: Mean Aggregation Number (N) Of Micellar Aggregates Supportedmentioning
confidence: 99%
“…The viscosity of the solutions renders the determination of the partition coefficient of DMBP between the micelles and the water phase impossible for our system at this polymer concentration. Van Stam et al reported a value of K D of 1900 M -1 for DMBP in 2% PEO and 20 mM SDS solution, where with [Q] m and [Q] aq the concentration of quencher in the micellar phase and in the water phase, respectively, and S m the concentration of surfactant in the micelles. For our system, S m can be expressed as S m = c p (M) + [SDS] m , where c p (M) is the concentration of hydrophobes from the polymer and [SDS] m is the concentration of SDS in the micelles.…”
Section: Resultsmentioning
confidence: 99%